Sebaceous nevus/Xanthogranuloma in plaque of the scalp. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2006)
Nevus sebaceous is a circumscribed, stable with time, hyperplasia of the epidermis and its adnexa. Juvenile xanthogranuloma is a benign proliferation of the first months of life, spontaneously regressing in about two years. Although the clinical course of sebaceous nevus and xanthogranuloma is very different, sometimes in the first months of life, due to the yellow color of both the disorders, some diagnostic problem may arise, especially when xanthogranuloma is not a tridimensional nodule.